Why the split of payroll taxation between firms and workers matters for macroeconomic stability - Simon Voigts (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Conventional wisdom states that the statutory split of payroll taxation between firms and workers is of no macroeconomic relevance, because the tax incidence is fully determined by the market structure. This paper breaks with this view by establishing a theoretical link between the statutory split and the average volatility of prices and wages. It is shown that shifting taxation towards workers significantly reduces the volatility in nominal variables without entailing long-run redistribution. The gain in stability of prices and wages reduces inefficiencies in the equilibrium allocation of the stochastic model and thereby reduces welfare costs of business cycle fluctuations. In a standard DSGE model, welfare costs un- der the full taxation of firms are 11.25% larger than under the full taxation of workers.
Keywords: H55; H21; E30; E32; E60; 330; payroll taxes; social security; business cycles; automatic stabilizers; optimal taxation